The Role of Net Profit Margin, Asset Turnover, and Equity Multiplier in Driving Stock Returns: Moderating Effect of ROE Dupont - Fajriyatul Abadiyah (Petra International Journal of Business Studies, 2023)
This study aims to test whether DuPont's ROE can moderate the effect of net profit margin, total asset turnover, and equity multiplier ratio on the stock returns of insurance companies listed on the Indonesia Stock Exchange. This research includes quantitative research. Purposive sampling techniques are used to find stocks of insurance companies that meet the research criteria. The data in this study is panel data sourced from financial statements and historical data on the closing prices of 14 insurance companies for the observation period of January 2018-December 2022. The research model uses SEM-PLS with a data analysis method, moderated regression analysis (MRA), through the Warp Pls 8.0 program. The results showed that the NPM variable did not affect stock returns, while TATO and EMR significantly affected insurance stock returns positively. Furthermore, Dupont's ROE moderation variable interactions were found to have varying classifications. Dupont's ROE role in NPM relationships acts as a homologizer, meaning it can influence the strength of the relationships built. While in the TATO relationship, Dupont's ROE acts as quasi-moderation, which means having a pseudo-interaction between the two. In the EMR relationship, Dupont's ROE acts as a moderation predictor, which means that Dupont's ROE variable only acts as an independent variable in the relationship model formed.